A Sinawali of Folklore, “History”, and Personal Narrative in Arnis - Pawilen, Ryan Alvin M. (BANWAAN: The Philippine Journal of Folklore, 2025)
This paper weaves folklore, historical narratives, and the author’s personal experience as an Arnis practitioner. The study aimed to present possible folklore materials shared in the Arnis community that the author identified during his years of training with this martial art. However, this paper does not claim to represent all Arnis styles, to provide a summary of all folklore materials in Arnis, nor to answer debates about the history of the art. This paper highlights the author’s experiences and reflections regarding the intersections of martial art, folklore, history, and personal narratives. Likewise, this paper attempts to show personal narratives as part of folklore both as a type of folk story as well as a method to transmit and sustain folklore in the Arnis community. To further adhere to this theme, autoethnography is utilized to present personal experiences. The analytic type of autoethnography was specifically used to contextualize personal narrative with the Arnis community and further address the reliability of the story. The analytic type of autoethnography also provided a means to present personal narratives as folklore following the characterization that folk stories must come from various sources in the group, creating a sense of shared experience. From this autoethnographic exploration, the author highlighted several aspects of Arnis training as a source of folklore. First is the historical narrative of the origins and the development of Arnis and the second is the actual training of Arnis itself. Keywords: Arnis, folklore, autoethnography, personal narrative, martial art, history